On normal lattices and separation and semi-separation of lattices - Robert W. Schutz (International Journal of Mathematics and Mathematical Sciences)
This present paper is concerned with two main conditions, that of normality of a lattice, and separation and semi-separation of two lattices, both looked at using measure theoretic techniques. We look at each property using {0,1} two valued measures and associated {0,1} valued set functions.